2011
DOI: 10.1139/p10-073
|View full text |Cite
|
Sign up to set email alerts
|

The two-photon approximation for the four-photon decay of the 4d excited state in hydrogenThis paper was presented at the International Conference on Precision Physics of Simple Atomic Systems, held at École de Physique, les Houches, France, 30 May – 4 June, 2010.

Abstract: The method of two-photon approximation for multiphoton decay is applied to the decay of the 4d state in the hydrogen atom. In the process of four-photon decay the two-photon contribution that leads to radiation escape, from the interaction with matter, is considered. This may be helpful for a strict description of the recombination process in the hydrogen atom and, in principle, for the history of hydrogen recombination in the early universe.PACS Nos: 98.70.Vc, 32.70.Cs, 32.80.Rm, Résumé : Nous utilisons l'app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Two-photon emission processes were evaluated accurately in [25][26][27]. In our recent works [28,29], three-and four-photon transitions with separation out of the two-photon links were considered from the astrophysical point of view. In [30,31] we considered one-and two-photon transitions in external electric fields.…”
Section: Introductionmentioning
confidence: 99%
“…Two-photon emission processes were evaluated accurately in [25][26][27]. In our recent works [28,29], three-and four-photon transitions with separation out of the two-photon links were considered from the astrophysical point of view. In [30,31] we considered one-and two-photon transitions in external electric fields.…”
Section: Introductionmentioning
confidence: 99%
“…In [34,35], it was suggested that the multiphoton transitions which contain cascades with the two-photon links can also contribute to the radiation 'escape' in the process of cosmological recombination. This approach was called 'twophoton approximation' since the contribution of the 'pure' multiphoton transitions with more than two photons was neglected.…”
Section: Contribution Of the Three-photon Transitionsmentioning
confidence: 99%
“…As in the case of three-photon decays, we neglect the contribution of the 'pure' four-photon decays and consider only the cascade contributions with two-photon links, namely 4s → 3p + γ (E1) → 2s + 2γ (E1) → 1s + 4γ (E1), 4s → 3s + 2γ (E1) → 2p + 3γ (E1) → 1s + 4γ (E1) and 4s → 3p + γ (E1) → 2p + 3γ (E1) → 1s + 4γ (E1). Then the expression similar to equation ( 40) arises [34,35]:…”
Section: Radiation 'Escape' In the Four-photon Transitionsmentioning
confidence: 99%
See 1 more Smart Citation